Investigating the impact of context and environment on driver's situation awareness. (September 2022) - Xing, Yilun; Park, Sami; Akash, Kumar; Wu, Xingwei; Misu, Teruhisa; Boyle, Linda Ng
The objective of this study is to assess drivers' ability to detect objects and the trajectory of these objects in scenarios with different environmental complexity levels. This is examined in the context of situation awareness (SA), defined as theperception, comprehension and projection of the environmental properties andpositions. The Situation Awareness Global AssessmentTechnique (SAGAT) was used in a video-based driving simulation study, where participants were asked to mark all objects in the order ofperceived risk and select the corresponding objecttype. This provided spatially continuous SA responses for the objects of interest (i.e., pedestrians, cars and cyclists). The findings showed that object type and size, visual complexity, number of objects and roadway typehada significant impact ontheoperator's ability toperceiveobjectsaswellastoprojectthe object trajectories. The resultsprovideus some insightsinchoosing predictorsbesideseye-tracking data for SA predictive model.